2014
DOI: 10.1111/1574-6968.12625
|View full text |Cite
|
Sign up to set email alerts
|

Gp66, a calcineurin family phosphatase encoded by mycobacteriophage D29, is a 2′, 3′ cyclic nucleotide phosphodiesterase that negatively regulates phage growth

Abstract: Mycobacteriophage D29 encodes a protein Gp66 which has been predicted to be a calcineurin family phosphoesterase. Phylogenetically Gp66 and related proteins mostly derived from mycobacteriophages form a distinct clade within this family. Interestingly, the presence of gene 66 orthologs can be traced to bacteria of diverse phylogenetic lineages such as Aquifex aeolicus, a deep branching eubacteria and Methanococcus jannaschii, an archaebacteria. The promiscuous nature of gene 66 suggests that it may have been t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A set of AMGs were identified from group I and II genomes, including genes encoding MPEs, amidoligase, GATase, 2OG-Fe(II) oxygenase, SufA, and Sulfotransferse. MPEs exhibit hydrolase activity against a wide range of phosphorylated substrates and are common in bacterial and archaeal genomes ( 54 56 ). Phage-encoded MPEs have been identified in many phage genomes ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A set of AMGs were identified from group I and II genomes, including genes encoding MPEs, amidoligase, GATase, 2OG-Fe(II) oxygenase, SufA, and Sulfotransferse. MPEs exhibit hydrolase activity against a wide range of phosphorylated substrates and are common in bacterial and archaeal genomes ( 54 56 ). Phage-encoded MPEs have been identified in many phage genomes ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…MPEs exhibit hydrolase activity against a wide range of phosphorylated substrates and are common in bacterial and archaeal genomes ( 54 56 ). Phage-encoded MPEs have been identified in many phage genomes ( 56 , 57 ). A previous study has suggested that Mycobacterium virus D29-encoded MPEs can negatively regulate the growth of bacteriophages and bacteria ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation